resin composition
Patent Information
- Application Number
- JP2026053733
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-28
- Filing Date
- 2026-03-27
- Publication Date
- 2026-10-13
AI Technical Summary
【0010】 本発明によれば、耐衝撃性及び透明性に優れるフィルムを形成し得る樹脂組成物を提供することができる。
Smart Images

Figure 2026165120000001
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition.
Background Art
[0002] In recent years, foldable display panels that can be repeatedly bent have been proposed for smartphones and tablet terminals, in order to achieve both larger screens and portability. Foldable display panels are required to be capable of repeated deformation between a bent shape and a flat, non-bent shape. In such display panels, repeated stress concentration occurs at the bent portion, and as a result, there are problems that the front plate may be damaged, the display itself may be damaged and stop displaying, and the impact when dropped or when writing with a stylus pen may be transmitted to the interior, affecting the display itself.
[0003] For example, Patent Documents 1 and 2 disclose films using an acrylic block copolymer containing a polymer block composed of structural units derived from methacrylic acid ester as a base resin, as impact-resistant films for use in front plates of foldable devices.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Patent Document 2
Summary of the Invention
Problem to be Solved by the Invention
[0005] However, films made solely from the base resin disclosed in Patent Documents 1 and 2 have the problem of insufficient impact resistance. Furthermore, films used for front panels of foldable devices are also required to have excellent transparency.
[0006] The present invention has been made in view of the above problems, and aims to provide a resin composition that can form a film with excellent impact resistance and transparency. [Means for solving the problem]
[0007] The inventors of the present invention have discovered that the above problems can be solved by using a resin composition containing specific additives, and have completed the present invention.
[0008] Aspects of this disclosure relate to the following resin compositions.
[0009] [1] An acrylic block copolymer (A) comprising a polymer block (a1) consisting of constituent units derived from methacrylic acid ester, A resin composition comprising a styrene-based resin (B) having a weight-average molecular weight of 700 or more and less than 4000, A resin composition in which the content of the polymer block (a1) is 35% by weight or more and less than 50% by weight relative to the total weight of the acrylic block copolymer (A). [2] The resin composition according to [1], wherein the acrylic block copolymer (A) comprises a polymer block (a2) consisting of constituent units derived from an acrylic acid ester. [3] The resin composition according to [2], wherein the weight ratio (a1) / (a2) of the polymer block (a1) to the polymer block (a2) is 20 / 80 to 50 / 50. [4] The resin composition according to [2] or [3], wherein the acrylic block copolymer (A) is a triblock copolymer consisting of polymer block (a1)-polymer block (a2)-polymer block (a1), or a diblock copolymer consisting of polymer block (a1)-polymer block (a2). [5] The resin composition according to [2] or [3], wherein the acrylic block copolymer (A) is a triblock copolymer consisting of polymer block (a1)-polymer block (a2)-polymer block (a1). [6] The resin composition according to any one of [1] to [5], wherein the acrylic block copolymer (A) has a Shore A hardness of 50 or more and 100 or less as measured in accordance with ISO 7619-1. [7] The resin composition according to any one of [1] to [6], wherein the styrene resin (B) is at least one selected from the group consisting of styrene-aromatic hydrocarbon copolymers, styrene-aliphatic hydrocarbon copolymers, styrene-(α-methylstyrene)-aliphatic hydrocarbon copolymers, styrene homopolymers, α-methylstyrene homopolymers, and styrene-(α-methylstyrene) copolymers. [8] The resin composition according to any one of [1] to [7], wherein the content of the styrene resin (B) is 10% by weight or more and 30% by weight or less with respect to the total weight of the acrylic block copolymer (A) and the styrene resin (B). [9] A resin composition according to any one of [1] to [8], for use in foldable devices.
[10] A resin composition according to any of [1] to [9], and a dope containing an organic solvent. A method for producing a resin film, comprising the step of casting the dope described in
[11]
[10] onto a support, and then evaporating the organic solvent. A resin film formed from the dope described in
[12]
[10] .
[13] The resin film described in
[12] , for use in foldable devices. [Effects of the Invention]
[0010] According to the present invention, it is possible to provide a resin composition that can form a film with excellent impact resistance and transparency. [Modes for carrying out the invention]
[0011] ≪Resin composition≫ The resin composition of this embodiment comprises an acrylic block copolymer (A) containing a polymer block (a1) made up of structural units derived from methacrylic acid ester, A resin composition comprising a styrene-based resin (B) having a weight-average molecular weight of 700 or more and less than 4000, The content of the polymer block (a1) is 35% by weight or more and less than 50% by weight relative to the total weight of the acrylic block copolymer (A).
[0012] According to the resin composition of this embodiment, since a resin composition containing a specific styrene-based resin (B) as an additive is used, it is possible to form a film that exhibits excellent impact resistance and transparency in the high-temperature range of the assumed operating temperature of the film, from 0°C to 60°C. The high-temperature range refers to 40°C to 60°C.
[0013] <Acrylic block copolymer (A)> From the viewpoint of the resulting film having excellent impact resistance, the resin composition includes an acrylic block copolymer (A) as a base resin, which contains a polymer block (a1) made up of structural units derived from methacrylic acid ester.
[0014] The constituent units derived from methacrylic acid esters (hereinafter also simply referred to as "methacrylic acid ester units") include methacrylic acid units, methyl methacrylate units; ethyl methacrylate units; propyl methacrylate units such as n-propyl methacrylate units and iso-propyl methacrylate units; butyl methacrylate units such as n-butyl methacrylate units, iso-butyl methacrylate units, sec-butyl methacrylate units and tert-butyl methacrylate units; pentyl methacrylate units; and ethyl methacrylate units. Examples include xyl units; cyclohexyl methacrylate units; heptyl methacrylate units; n-octyl methacrylate units, 2-ethylhexyl methacrylate units, and other octyl methacrylate units; nonyl methacrylate units; decyl methacrylate units; undecyl methacrylate units; dodecyl methacrylate units; tridecyl methacrylate units; tetradecyl methacrylate units; hexadecyl methacrylate units; octadecyl methacrylate units; and alkyl methacrylate units such as eicosyl methacrylate units. Among these, homopolymers or copolymers consisting of monomers such as methyl methacrylate units are preferred, and homopolymers or copolymers consisting of monomers of methyl methacrylate units are particularly preferred.
[0015] Examples of acrylic block copolymers (A) include copolymers in which the polymer block (a1) contains structural units derived from methacrylic acid ester, and other structural units include structural units derived from acrylonitrile, structural units derived from ethylene, or structural units derived from acrylic acid ester. Among these, structural units derived from acrylic acid ester are preferred.
[0016] The structural unit derived from an acrylate ester (hereinafter also simply referred to as "acrylate ester unit") includes acrylic acid units, methyl acrylate units; ethyl acrylate units; propyl acrylate units such as n-propyl acrylate units and iso-propyl acrylate units; butyl acrylate units such as n-butyl acrylate units, iso-butyl acrylate units, sec-butyl acrylate units and tert-butyl acrylate units; pentyl acrylate units; hexyl acrylate units; cyclohexyl acrylate units; heptyl acrylate units; octyl acrylate units such as n-octyl acrylate units and 2-ethylhexyl acrylate units; nonyl acrylate units; decyl acrylate units; undecyl acrylate units; dodecyl acrylate units; tridecyl acrylate units; tetradecyl acrylate units; hexadecyl acrylate units; octadecyl acrylate units; alkyl acrylate units such as icosyl acrylate units, and the like. Among these, a homopolymer or copolymer composed of monomers such as n-butyl acrylate units and 2-ethylhexyl acrylate units is preferred, and a homopolymer or copolymer composed of the monomer of n-butyl acrylate units is particularly preferred.
[0017] Hereinafter, the polymer block containing the structural unit derived from an acrylate ester is also referred to as "polymer block (a2) composed of the structural unit derived from an acrylate ester".
[0018] From the viewpoint of excellent impact resistance of the resulting film, the content of the polymer block (a1) is preferably 35% by weight or more and less than 50% by weight, more preferably 35% by weight or more and 49% by weight or less, even more preferably 36% by weight or more and 48% by weight or less, and still more preferably 37% by weight or more and 46% by weight or less, based on the total weight of the acrylic block copolymer (A). Further, as the acrylic block copolymer (A), a plurality of acrylic block copolymers (A) having different contents of the polymer block (a1) may be used as a mixture, and by mixing these, the content of the polymer block (a1) can also be adjusted to the above range.
[0019] The acrylic block copolymer (A) preferably comprises a polymer block (a1) composed of structural units derived from a methacrylic acid ester and a polymer block (a2) composed of structural units derived from an acrylic acid ester. The weight ratio (a1) / (a2) of the polymer block (a1) to the polymer block (a2) is preferably 20 / 80 to 50 / 50, more preferably 30 / 70 to 49 / 51, even more preferably 35 / 65 to 48 / 52, and still more preferably 37 / 63 to 46 / 54.
[0020] The acrylic block copolymer (A) is preferably a triblock copolymer consisting of polymer block (a1)-polymer block (a2)-polymer block (a1), or a diblock copolymer consisting of polymer block (a1)-polymer block (a2). Among these, a triblock copolymer is more preferred.
[0021] The above resin preferably has a Shore A hardness of 50 or more and 100 or less, measured in accordance with ISO 7619-1. From the viewpoint of achieving an excellent balance between impact resistance and hardness of the film, the Shore A hardness of the resin is preferably 55 or more and 90 or less, more preferably 60 or more and 85 or less, and even more preferably 65 or more and 80 or less.
[0022] Examples of commercially available products of the acrylic block copolymer (A) include KURARITY LA2270 and LB550 manufactured by Kuraray Co., Ltd., and Nanostrength M51, D51N, M52, M52N, M53, M55, M65, M65N and the like manufactured by Arkema S.A.
[0023] <Styrenic Resin (B)> The above resin composition contains a styrene resin (B) as an additive, in addition to the aforementioned acrylic block copolymer (A). The styrene resin (B) has good compatibility with the acrylic block copolymer (A). By using a resin composition containing both the acrylic block copolymer (A) and the styrene resin (B), the impact resistance of the film is improved while maintaining the transparency of the film, compared to when the acrylic block copolymer (A) is used alone.
[0024] (Styrene resin (B)) The weight-average molecular weight of the styrene resin (B) is preferably 700 or more and less than 4000, more preferably 800 or more and 3000 or less, more preferably 900 or more and 2500 or less, and even more preferably 1000 or more and 2200 or less, from the viewpoint of the resulting film having excellent impact resistance, transparency, and bleed-out resistance.
[0025] The styrene-based resin (B) is preferably at least one selected from the group consisting of styrene-aromatic hydrocarbon copolymers, styrene-aliphatic hydrocarbon copolymers, styrene-(α-methylstyrene)-aliphatic hydrocarbon copolymers, styrene homopolymers, α-methylstyrene homopolymers, and styrene-(α-methylstyrene) copolymers.
[0026] As styrene-aromatic hydrocarbon copolymers, FMR-0150 (softening point 145°C, manufactured by Mitsui Chemicals, Inc.) can be used. As styrene-aliphatic hydrocarbon copolymers, FTR-6100 (manufactured by Mitsui Chemicals, Inc.), FTR-6110 (manufactured by Mitsui Chemicals, Inc.), FTR-6125 (manufactured by Mitsui Chemicals, Inc.), etc. can be used. As styrene-(α-methylstyrene)-aliphatic hydrocarbon copolymers, FTR-7100 (manufactured by Mitsui Chemicals, Inc.), etc. can be used. As styrene homopolymers (or styrene-based polymers), FTR-8120 (manufactured by Mitsui Chemicals, Inc.), etc. can be used. As α-methylstyrene homopolymers (or α-methylstyrene-based polymers), FTR-0100 (manufactured by Mitsui Chemicals, Inc.), etc. can be used. Examples of styrene-(α-methylstyrene) copolymers that can be used include FTR-2120 (manufactured by Mitsui Chemicals), FTR-2140 (manufactured by Mitsui Chemicals), Kristalex1120 (manufactured by Eastman Chemicals), Kristalex3070 (manufactured by Eastman Chemicals), Kristalex3085 (manufactured by Eastman Chemicals), and Kristalex3100 (manufactured by Eastman Chemicals).
[0027] In the resin composition, the content of styrene resin (B) is preferably 10% to 30% by weight, more preferably 13% to 30% by weight, and even more preferably 16% to 30% by weight, based on the total weight of the acrylic block copolymer (A) and the styrene resin (B).
[0028] (Other ingredients) The resin composition may contain components other than the acrylic block copolymer (A) and styrene resin (B) (hereinafter also referred to as "other components"), as long as they do not impair the effects of the present invention. Examples of other components include lubricants, nucleating agents, ultraviolet absorbers, light stabilizers, flame retardants, stabilizers, antistatic agents, plasticizers, crosslinking agents, crosslinking aids, photosensitizers, tackifiers, pigments, dyes, organic fillers, inorganic fillers, silane coupling agents, titanium coupling agents, and other additives, polymerizable group-containing compounds, polymerization initiators, and the like. These other components may be used individually or in combination of two or more.
[0029] (Application) As described above, the resin composition can form a film with excellent impact resistance and transparency. For this reason, it can be suitably used for foldable devices.
[0030] ≪Dope≫ The dope of this embodiment comprises the aforementioned resin composition and an organic solvent. The dope is used to manufacture the resin film described later by a solution casting method. Examples of organic solvents include ketone solvents such as methylene chloride, acetone, and methyl ethyl ketone; ester solvents such as ethyl acetate and ethyl propionate; and amide solvents such as dimethylformamide and dimethylacetamide.
[0031] The solid content concentration in the dope is preferably 10% by weight or more and 60% by weight or less, and preferably 15% by weight or more and 50% by weight or less, based on the total weight of the dope.
[0032] ≪Resin film≫ The resin film of this embodiment is formed from the dope described above. The resin film may be manufactured by either the melt extrusion method or the solution casting method. When manufactured by the solution casting method, the process includes casting the dope onto a support and then evaporating the organic solvent contained in the dope. Specifically, for example, the process includes preparing a dope by dissolving a resin composition in an organic solvent, casting the dope onto a PET film as a support, then casting the coating solution in a uniform film shape using a bar coater or comma coater so that the thickness after drying is approximately 15 μm to 300 μm, and then drying the coating film.
[0033] <Film properties> (loss tangent (tanδ)) The tanδ of the obtained resin film is one of the indicators of the film's impact resistance; a larger tanδ means the film has superior impact resistance. The tanδ at 0°C, 25°C, 40°C, and 60°C are indicators of the film's impact resistance at assumed operating temperatures from low to high temperatures, and the average value of tanδ, which represents the average of these four temperatures, indicates the impact resistance across the entire range of assumed operating temperatures. When dynamic viscoelasticity measurements were performed in tensile mode on the obtained resin film with a thickness of 150 μm at a vibration frequency of 100 Hz and a temperature range of 0°C to 60°C, the average value of the loss tangent (tanδ) at 0°C, 25°C, 40°C, and 60°C is preferably 0.2 to 0.6, more preferably 0.24 to 0.6, even more preferably 0.28 to 0.6, and even more preferably 0.32 to 0.6. The obtained resin film exhibits superior impact resistance in the high-temperature range of its assumed operating temperature of 0°C to 60°C. "High temperature range" refers to temperatures between 40°C and 60°C. The "film with a thickness of 150 μm" mentioned above refers to the film thickness used when measuring the loss tangent (tanδ). As will be described later, the thickness of the resin film in this embodiment is not particularly limited, but is preferably within the range of 15 μm to 300 μm.
[0034] (Hayes) The haze of the resulting resin film with a thickness of 150 μm is preferably 0.01% to 2.0%, more preferably 0.01% to 1.5%, even more preferably 0.01% to 1.0%, and even more preferably 0.01% to 0.9% from the viewpoint of the film having excellent transparency. The haze is measured using a haze meter. The "resin film with a thickness of 150 μm" mentioned above refers to the film thickness used when measuring haze. As will be described later, the thickness of the resin film in this embodiment is not particularly limited, but is preferably within the range of 15 μm to 300 μm.
[0035] The thickness of the resin film is preferably in the range of 15 μm to 300 μm, more preferably 20 μm to 200 μm, and particularly preferably 25 μm to 150 μm. A film thickness of 300 μm or more is undesirable because it increases the stress generated at the bent portion. Also, if the film thickness is less than 15 μm, the film may become difficult to handle.
[0036] (Application) As mentioned above, resin films have excellent impact resistance and transparency. For this reason, resin films can be suitably used for foldable devices. [Examples]
[0037] The present invention will be described more specifically below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0038] <Ingredients> In the examples and comparative examples, the following A1 to A11 were used as the base resin. A1: Acrylic block copolymer (manufactured by Kuraray Co., Ltd., Clarity 2270, MMA ratio 38% by weight, Shore A hardness 71) A2: Acrylic block copolymer (manufactured by Kuraray Co., Ltd., Clarity 4285, MMA ratio 50% by weight, Shore A hardness 95) A3: Acrylic block copolymer (Kuraray Co., Ltd., Clarity LB550, MMA ratio 40% by weight, Shore A hardness 78) A4: Acrylic block copolymer (Kuraray Co., Ltd., Clarity 2330, MMA ratio 20% by weight, Shore A hardness 32) A5: Hydrogenated styrene-based thermoplastic elastomer (Kuraray Co., Ltd., Septon 2002, Shore A hardness 80) A6: Hydrogenated styrene-based thermoplastic elastomer (Kuraray Co., Ltd., Septon 2140) A7: Hydrogenated styrene-based thermoplastic elastomer (Kuraray Co., Ltd., Septon 2104, Shore A hardness 98) A8: Thermoplastic polyester elastomer (manufactured by Toray Celanese, Hytrel 4057) A9: Thermoplastic polyurethane (Pandex T8195, manufactured by DIC Covestropolymer Corporation) A10: Thermoplastic polyurethane (Desmopan 88385, manufactured by DIC Covestropolymer Corporation) A11: Acrylic block copolymer (Arkema, Nano Strength M65, MMA ratio 40%, Shore A hardness 55) *The "MMA ratio" for A1-A4 and A11 indicates the content of polymer blocks consisting of methyl methacrylate units relative to the total weight of each base resin.
[0039] In the examples and comparative examples, the following additives B1 to B10 were used. B1: Low molecular weight polystyrene (manufactured by Sanyo Chemical Industries, Ltd., Hymer ST95, weight-average molecular weight: 4000) B2: Styrene resin (manufactured by Mitsui Chemicals, FTR8120, weight-average molecular weight: 1420) B3: Styrene resin (manufactured by Mitsui Chemicals, FTR6125, weight-average molecular weight: 1950) B4: Styrene resin (manufactured by Mitsui Chemicals, FMR0150, weight-average molecular weight: 1190) B5: Polyethylene glycol (manufactured by Fujifilm & Wako Pure Chemical Industries, Ltd., PEG4000, weight-average molecular weight: 2700-3300) B6: Acrylic copolymer (manufactured by Mitsubishi Gas Chemical Company, OPTIMAS) B7: Benzotriazole compound (BASF Japan, Tinuvin 329, molecular weight: 329)
[0040] <Doping test> Base resins A1-A11 and additives B1-B7 were weighed to the weights listed in Table 1 and placed in glass bottles. Methylene chloride was added to a solid content concentration of 35 wt% to prepare the dope. A stirring bar was placed in the resulting dope and stirred at 300 rpm for 30 minutes at room temperature using a magnetic stirrer. After standing for 30 minutes, the dope was visually observed and evaluated based on the following criteria. (Evaluation Criteria) ○: No insoluble material was found, and a transparent dope was observed. ×: Insoluble material was observed, and opaque doping was observed.
[0041] For the base resins A1-A4, A6-A7, A9-A11, and additives B1-B5 and B7, which yielded good results (evaluation: ○) in the doping test, the following films were fabricated and their physical properties were measured.
[0042] <Film production> (Example 1) A mixture of 90% by weight of base resin A1 and 10% by weight of additive B2 was dissolved in methylene chloride to prepare a dope with a solid content concentration of 35 wt%. The prepared dope was cast onto a biaxially oriented polyethylene terephthalate film (Therapyel® PJ101 (manufactured by Toray Industries, Inc.), hereinafter referred to as PET film), and the coating solution was then applied uniformly to a film with a bar coater so that the thickness after drying was approximately 150 μm. The film was laid on a support and baked in a 60°C oven for 5 minutes. Subsequently, it was peeled off the support, fixed to a metal frame with tape on all four sides, and dried at 80°C for 5 minutes and then at 100°C for 5 minutes to obtain a film with a thickness of approximately 150 μm.
[0043] (Examples 2-7, Comparative Examples 1-16) A film was prepared using the same method as in Example 1, except that the type of base resin and additives, and their content, were changed to those listed in Table 1.
[0044] <Rating> (loss tangent (tanδ)) For each obtained film, the loss tangent (tanδ) was measured in tensile mode at 100 Hz, -40°C to 120°C using a dynamic viscoelasticity analyzer (DMS6100, manufactured by SII Nanotechnology Co., Ltd.). The arithmetic mean of the loss tangent (tanδ) at 0°C, 25°C, 40°C, and 60°C was then calculated. The measurement conditions are shown below. Sample: Width 9mm, distance between gripping parts 20mm Measurement temperature range: -40℃ to 120℃ Heating rate: 3°C / min Atmosphere: The atmosphere is low. Distortion amplitude: 30 μm Measurement frequency: 100Hz Minimum tension / compression force: 100mN Tension / compression gain: 1.5 Initial force amplitude: 100mN~300mN
[0045] (Hayes) Each obtained film was measured using a haze meter (HAZEMETER HM-150N, manufactured by Murakami Color Technology Laboratory) in accordance with JIS-K-7361-1.
[0046] [Table 1]
[0047] Table 1 shows that films obtained from the resin compositions of Examples 1 to 7 have an average loss tangent (tanδ) of 0.2 or higher at 0°C, 25°C, 40°C, and 60°C, exhibiting excellent impact resistance, haze of 2.0% or less, and excellent transparency.
Claims
1. An acrylic block copolymer (A) comprising a polymer block (a1) consisting of constituent units derived from methacrylic acid ester, A resin composition comprising a styrene-based resin (B) having a weight-average molecular weight of 700 or more and less than 4000, A resin composition in which the content of the polymer block (a1) is 35% by weight or more and less than 50% by weight relative to the total weight of the acrylic block copolymer (A).
2. The resin composition according to claim 1, wherein the acrylic block copolymer (A) comprises a polymer block (a2) consisting of structural units derived from an acrylic acid ester.
3. The resin composition according to claim 2, wherein the weight ratio (a1) / (a2) of the polymer block (a1) to the polymer block (a2) is 20 / 80 to 50 / 50.
4. The resin composition according to claim 2 or 3, wherein the acrylic block copolymer (A) is a triblock copolymer consisting of polymer block (a1) - polymer block (a2) - polymer block (a1), or a diblock copolymer consisting of polymer block (a1) - polymer block (a2).
5. The resin composition according to claim 4, wherein the acrylic block copolymer (A) is a triblock copolymer consisting of polymer block (a1) - polymer block (a2) - polymer block (a1).
6. The resin composition according to claim 1 or 2, wherein the acrylic block copolymer (A) has a Shore A hardness of 50 or more and 100 or less, as measured in accordance with ISO 7619-1.
7. The resin composition according to claim 1 or 2, wherein the styrene-based resin (B) is at least one selected from the group consisting of styrene-aromatic hydrocarbon copolymers, styrene-aliphatic hydrocarbon copolymers, styrene-(α-methylstyrene)-aliphatic hydrocarbon copolymers, styrene homopolymers, α-methylstyrene homopolymers, and styrene-(α-methylstyrene) copolymers.
8. The resin composition according to claim 1 or 2, wherein the content of the styrene resin (B) is 10% by weight or more and 30% by weight or less with respect to the total weight of the acrylic block copolymer (A) and the styrene resin (B).
9. A resin composition according to any one of claims 1 to 3, for use in foldable devices.
10. A resin composition according to any one of claims 1 to 3, and a dope comprising an organic solvent.
11. A method for producing a resin film, comprising the step of casting the dope described in claim 10 onto a support, and then evaporating the organic solvent.
12. A resin film formed from the dope described in claim 10.
13. A resin film according to claim 12, for use in a foldable device.
Citation Information
Patent Citations
Front plate for foldable device and foldable device
JP2024062966A
Adhesive-layer-equipped elastic sheet, and flexible display device in which same is used
WO2022181656A1